INTEGRASI KONSEP ISLAMI DAN KONSEP ARSITEKTUR MODERN PADA PERANCANGAN ARSITEKTUR MASJID - Umar, Umar (Universitas Bina Taruna Gorontalo, 2014)
ABSTRACK The basic concept of mosque architectural design based on Indonesian Islamic culture which up until now was regarded as an in independent approach as if no other choice in mosque designing. There is a challenge in designing process which open the opportunity to explore the more creative and innovative ideas. This new concept will reveal new perspective in design approach process. The attempt to search various resources in the process would make architecture designer expand their perception idea on mosque design. So far, the Indonesian architectural mosque has been considered to have solid and rigid concept with the dome. This study analyzes the issues of mosque architectural designing approach which have new innovative and creative design.The understanding of Islamic concept here is focused on its spiritual philosophy. Deep comprehension in Islamic concept has similarity in enthusiasm with modern architectural design concept. So the integration of both architectural Islamic design and modern architectural design concept would work sinergically and inspire new perspective in mosque designing.Hopelly, the same effort would be made by the architect or designer in design process in developing and creating the new concept, so the creative process would have more freedom Keyword: Islamic concept, Modern architecture concept, Mosque architecture project